Combined Effects of Mother’s, Father’s and Teacher’s Psychological Distress on Schoolchildren’s Mental Health Symptoms - Li S (Dove Medical Press, 2021)
Shuang Li,1,2 Jun Na,1,2 Huijuan Mu,1,2 Yanxia Li,1,2 Li Liu,1,2 Rui Zhang,1,2 Jingyan Sun,1,3 Yuying Li,1,3 Wei Sun,1,3 Guowei Pan,1,3 Lingjun Yan1,3 1Institute of Preventive Medicine, China Medical University, Shenyang, People’s Republic of China; 2Institute of Chronic Diseases, Liaoning Provincial Center for Disease Control and Prevention, Shenyang, People’s Republic of China; 3Research Center for Universal Health, School of Public Health, China Medical University, Shenyang, People’s Republic of ChinaCorrespondence: Lingjun YanResearch Center for Universal Health, School of Public Health, China Medical University, No. 77 Puhe Road, Shenyang North New Area, Shenyang, Liaoning, 110122, People’s Republic of ChinaTel + 86 2431939406Email ljyan@cmu.edu.cnPurpose: Few studies have assessed the individual and joint effects of the mother’s, father’s and teacher’s mental health symptoms on schoolchildren’s behavior and emotional well-being simultaneously in the same study.Patients and Methods: A cross-sectional survey was conducted among 8488 Chinese schoolchildren aged 6– 17 years in northeast China. The Strengths and Difficulties Questionnaire (SDQ) and General Health Questionnaire (GHQ) were used to measure the mental health of the students, their parents and the teacher in charge of the class, respectively. A total of 6173 students (72.73%) with full mental health information from all three caretakers were included in the final analysis.Results: We found a significantly elevated risk of mental health symptoms in children when their mothers (odds ratios (OR)=2.30, 95% CI=1.93– 2.73), fathers (OR=2.08, 95% CI=1.73– 2.50) and teachers (OR=1.18, 95% CI=1.01– 1.39) reported poorer mental health, and the risk increased significantly with the number of the caretakers with mental symptoms. A father with poor mental health has both direct and indirect effects on a child’s emotional health, by worsening the influence of a mother’s poor mental health.Conclusion: All three caretakers have a significant negative influence on schoolchildren’s emotional well-being, in the order of mother > father > teacher. It is desirable to assess and manage students’ mental health in the both the family and school contexts.Keywords: combined effects, mental health symptoms, fathers, mothers, teachers, school children